2019
DOI: 10.1001/jamaneurol.2019.0098
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Morbidity and Outcomes Associated With Use of Subdural Grids vs Stereoelectroencephalography in Patients With Intractable Epilepsy

Abstract: IMPORTANCE A major change has occurred in the evaluation of epilepsy with the availability of robotic stereoelectroencephalography (SEEG) for seizure localization. However, the comparative morbidity and outcomes of this minimally invasive procedure relative to traditional subdural electrode (SDE) implantation are unknown. OBJECTIVE To perform a comparative analysis of the relative efficacy, procedural morbidity, and epilepsy outcomes consequent to SEEG and SDE in similar patient populations and performed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
129
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(138 citation statements)
references
References 88 publications
4
129
1
4
Order By: Relevance
“…Neural data from depth and surface grid electrodes are comparable given the identical contact material, similar surface area, and identical recording hardware. The relative proportion of depth probe and grid electrode implants reflects the major improvements in patient safety and outcome afforded by recent advances in stereotactic electroencephalography 69 .…”
Section: Methodsmentioning
confidence: 99%
“…Neural data from depth and surface grid electrodes are comparable given the identical contact material, similar surface area, and identical recording hardware. The relative proportion of depth probe and grid electrode implants reflects the major improvements in patient safety and outcome afforded by recent advances in stereotactic electroencephalography 69 .…”
Section: Methodsmentioning
confidence: 99%
“…Assuming these safety considerations are met, the complication rates from SEEG have been shown to be generally low: Mullin et al reported a pooled complication prevalence of 1.3% (hemorrhage, 1%; infection, 0.8%; electrode malpositioning, 0.6%; hardware malfunction, 0.4%; and death, 0.3%) (14), and Cardinale et al reported an overall complication prevalence of 1.8% [three major complications (0.4%) and one fatality (0.1%)] (9). Additionally, SEEG has been shown to have lower morbidity and higher tolerability by patients than subdural electrodes or intraoperative ECoG (13,15). Beyond the safety considerations, additional factors related to the electrical stimulation of neural tissue must be addressed, namely, charge density and charge per phase (1).…”
Section: Current Practice and Decision-making For The Use Of Seeg Stimentioning
confidence: 99%
“…Patient-level variables included patient age, sex, invasive monitoring technique, resection status and location, and pathology, and were selected based on current literature describing their association with patient outcomes. 8 Nation-level covariates were divided into five categories: (1) health & health care, (2) economy & growth, (3) education, (4) environment & poverty, and (5) science & technology. The covariate of neurosurgeon density per 100 000 population was included in the category of health and health care and was analyzed separately from the covariate of physician density per 100 000 population.…”
Section: Explanatory Variablesmentioning
confidence: 99%